ANALYSIS OF THE INFLUENCE OF PRINCIPAL LEADERSHIP, TEACHER COMMITMENT AND SCHOOL CULTURE ON THE PERFORMANCE OF TEACHERS OF MAN 4 TABALONG, TABALONG REGENCY - Muhammad Nor; Anthonius Junianto Karsudjono (INFOKUM, 2022)
The purpose of this study was to find out: (1) Principal Leadership, Teacher Commitment and School Culture simultaneously influence the Performance of MAN 4 Tabalong Teachers, Tabalong Regency, (2) Work enthusiasm, work professionalism and work ability partially influence MAN Teacher Performance 4 Tabalong, Tabalong Regency, (3) sees the most dominant influence on performance. The data collection method used in this study was a questionnaire method with a total of 32 (thirty two) respondents. The sampling method used is the census method because the entire population is sampled. The analysis technique used in this study is multiple regression analysis which previously tested the validity, reliability and classical assumptions (Multicollinearity, Heteroscedasticity, Autocorrelation, Normality and Linearity). The results of the study show the simultaneous and partial influence of the Principal's Leadership, Teacher Commitment and School Culture on the Performance of Population and Civil Registration Teachers in Tabalong Regency. Teacher commitment is the most dominant variable affecting teacher performance at MAN 4 Tabalong, Tabalong Regency.